Population genetics of Camellia granthamiana, an endangered plant species with extremely small populations in China - Chen, Sufang; Li, Wenyan; Li, Wei; Liu, Zhongcheng; Shi, Xianggang; Zou, Yanli; Liao, Wenbo; Fan, Qiang (Frontiers in Genetics, 2023)
Camellia, the largest genus of Theaceae, is well-known for having high economic values. Camellia granthamiana demonstrates large beautiful flowers with some primitive characters, such as multiple large and persistent bracteoles and sepals, was listed as Vulnerable species in the IUCN Red List. In this study, we investigated all possible records of the species, and sampled four natural populations and five cultivated individuals. By applying shallow-genome sequencing for nine individuals and RAD-seq sequencing for all the sampled 77 individuals to investigate population genetic diversity and population structure of the species. The results showed that the population sampled from Fengkai, previously identified as C. albogigias, possessed different plastid genome from other species possibly due to plastid capture; the species possesses strong population structure possibly due to habitat fragmentation and self-crossing tendency of the species, whose effective population size declined in the past 4,000 years. Nevertheless, C. granthamiana maintains a medium level of genetic diversity within population, and significant differentiation was observed among the four investigated populations, it is proposed that more populations are expected to be found and all these extant populations should be taken into instant protection.